Ozonised Saline Solution in treating Post-EBV-Fatigue Syndrome. Case Report and review of the literature (Ozone Therapy Global Journal, 2022)
Context: Currently, there is no effective antiviral therapy recommended for Chronic-Epstein- Barr-Virus Syndrome or for Post-Epstein-Bar-Virus Fatigue SyndromeAims: To assess the efficacity of ozonised saline solution(O3SS) used as a complementary therapy in adults who suffer from -Epstein-Bar-Virus Fatigue Syndrome or from Chronic-Epstein- Barr-Virus SyndromeMethods: Ten adult patients with chronic fatigue symptoms since their EBV-infection (>6 months) were included in this observational case study. Prior to initiating, and two weeks after treatment the Fatigue Severity Scale and lab values to monitor the changes in EBV-VAC-IgG, EBV-VAC-NA, EBV-EA, EBV IgM, Th1 , Th2, CD4 and CD8 were obtained. Patients were treated with O3SS, six sessions at a rate of three sessions a week then four sessions at a rate of two sessions a week (ten sessions in total). No control group was included. Secondary endpoints assessed included the fatigue score of participants and laboratory examinations.Results: O3SS treatment demonstrated a significant (p